2020
DOI: 10.3389/fneur.2020.00865
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Serial Nerve Ultrasound in Miller Fisher Syndrome

Abstract: Objective: Miller Fisher syndrome (MFS) is predominantly a clinical diagnosis, with classic triad of ophthalmoplegia, ataxia, and generalized reduced reflexes. Previous studies in chronic and acute immune-mediated neuropathies indicated that ultrasound, may help to detect changes that could correspond with disease activity. We studied the feasibility of serial nerve ultrasound in MFS, using a healthy controls. Methods: All MFS patients (n = 5) and healthy controls (n = 18), underwent a standardized sonographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…MFS is a rare variant of Guillain-Barré syndrome (GBS), an autoimmune disease of the peripheral nervous system (Al Othman et al 2019 ; Gómez et al 2019 ; Hsueh et al 2020 ). MFS is characterized symptomatically by ophthalmoplegia, ataxia, and areflexia and biochemically by elevated cerebrospinal fluid (CSF) protein concentration and the presence of autoantibody against ganglioside GQ1b, which is abundant in the paranodal region at the nodes of Ranvier along myelinated axons (Arányi et al 2012 ; Heckmann and Dütsch 2012 ; Teener 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…MFS is a rare variant of Guillain-Barré syndrome (GBS), an autoimmune disease of the peripheral nervous system (Al Othman et al 2019 ; Gómez et al 2019 ; Hsueh et al 2020 ). MFS is characterized symptomatically by ophthalmoplegia, ataxia, and areflexia and biochemically by elevated cerebrospinal fluid (CSF) protein concentration and the presence of autoantibody against ganglioside GQ1b, which is abundant in the paranodal region at the nodes of Ranvier along myelinated axons (Arányi et al 2012 ; Heckmann and Dütsch 2012 ; Teener 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to simple paralysis of the ocular muscles, weakness of the oropharyngeal–cervical muscles (7, 46.67%) was also seen more frequently in our patients, in agreement with the 50% (3/6) reported in a previous study in the Indian region regarding GBS [ 23 ], and higher than that in childhood [ 24 ]. Eight patients had facial muscle weakness (8, 53.33%), while the five patients with COVID-19 reported by Toscano et al in Guillain–Barré syndrome (GBS) had four cases of facial biparesis (80%) [ 25 ], and this percentage was similar to MFS (4/5, 80%) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…130 Miller Fisher Syndrome (MFS) is a rare GBS variant characterised by the triad of ophthalmalgia, ataxia and areflexia, and is often associated with bilateral facial weakness. Hsueh et al 132 reported significantly enlarged facial but normal limb nerves in MFS.…”
Section: Dovepressmentioning
confidence: 98%